Regional economic achievements and reindustrialisation in Hajdú-Bihar county - Nagy, János; Sinóros-Szabó, Botond; Harsányi, Endre; Nagy, Orsolya; Harsányi, Endre (Acta Agraria Debreceniensis, 2014)
The North Great Plain region is one of the backward regions of Hungary. The low level of economic development is mainly due to the lack of industrial development. The region is poor in natural resources, its main resources are land, natural gas fields, carbon dioxide, thermal water and the clay mineral stock.The structure of GDP per capita of the county is different than the country average mainly because of the high proportion of agriculture.The proportion of the industry and the building industry is not significant. Of the various service provider sectors, trade, transport and telecommunications have a small proportion, while financial and economic service providers have even lower share, which is due to the fact that these sectors are mostly concentrated in Budapest. The share of public and human service prodivers is higher than average due to the University of Debrecen.The GDP which expresses the economic development of the county in a complex way increased four times its previous value in nominal value between 1995–2009. However, if the real value is considered, the increase is less than 25%, as opposed to the country average, which was less than 40%.The most complex index of the development level of an economy is GDP expressed either in nominal or real value. If expressed in dollars, GDP is suitable for international comparison with the correction based on the purchasing power parity per person.The county represents 4.3% of the people employed in the industrial sector in Hungary, while its share in industrial production is only 3.3% which is lower than the regional and population share of the county within Hungary. As regards industrial production per person, Hajdú-Bihar was the 10th county in Hungary; therefore, it is considered to be a less industrialised county.The product structure of GDP is suitable for drawing useful development conclusions, but the result is more reliable if the income creation ability is also analysed on the basis of the employment structure.